2021
DOI: 10.30812/humanitatis.v7i2.1248
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis on Students’ Difficulties in Speaking

Abstract: The purpose of this research was to analyze the students’ difficulties in speaking English especially in introducing them self at MTS NW Al Hidayah Baremayung. Besides, the researcher also wanted know what the students’ difficulties in speaking English and what the factors of students difficulties in speaking English especially in introducing them self. The method of collecting data are observation, recording, and interview. The data were taken from the subject of the research in the form of teaching learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Another significant benefit of using flashcard in speaking practice for twelve grader students is to avoid student's anxiety in speaking due to lack of vocabulary. According to Handini (2021), some of the obstacles making students speechless is due to difficulty to select dictions and produce words correctly. These obstacles worsened the student's fluency as the become more anxious and lack of self confidence to express themselves (Abin & Meisi, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Another significant benefit of using flashcard in speaking practice for twelve grader students is to avoid student's anxiety in speaking due to lack of vocabulary. According to Handini (2021), some of the obstacles making students speechless is due to difficulty to select dictions and produce words correctly. These obstacles worsened the student's fluency as the become more anxious and lack of self confidence to express themselves (Abin & Meisi, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…According to Rianti (2021), "Simple past tense is a verb that is used to talk about things that happened or existed before now. It may be inferred from the theories and viewpoints presented that the simple past tense relates to the beginning and end of an activity or circumstance at a specific time in the past.…”
Section: Simple Past Tensementioning
confidence: 99%
“…Speaking skill in English is a person's skill to convey their desires and thoughts to anyone verbally, (Handini et al, 2021) also stated that speaking enables people to send and receive information or messages to others. Unfortunately, in Indonesia mastering speaking skill is not easy, it was found that most of the students still have difficulties to speak English.…”
Section: Introductionmentioning
confidence: 99%